Polyanion-type cathode materials for sodium-ion batteries - Jin, Ting; Li, Huangxu; Zhu, Kunjie; Wang, Peng-Fei; Liu, Pei; Jiao, Lifang (Chemical Society reviews, 2020)
Room-temperature sodium-ion batteries (SIBs) are regarded as promising candidates for smart grids and large-scale energy storage systems (EESs) due to their significant benefits of abundant and low-cost sodium resource. Among the previously reported cathode materials for SIBs, layered transition-metal oxides and polyanion-type materials are considered to be the most attractive options. Although many layered transition-metal oxides can provide high capacity due to their small molecular weight, their further application is hindered by low output voltage (mostly lower than 3.5 V), irreversible phase transition as well as storage instability. Comparatively, polyanion-type materials exhibit higher operating potentials due to the inductive effect of polyanion groups. Their robust 3D framework significantly decreases the structural variations during sodium ion de/intercalation. Moreover, the effect of strong X-O (X = S, P, Si, etc. ) covalent bonds can effectively inhibit oxygen evolution. These advantages contribute to the superior cycle stability and high safety of polyanion-type materials. However, low electronic conductivity and limited capacity still restrict their further application. This review summarizes the recent progress of polyanion-type materials for SIBs, which include phosphates, fluorophosphates, pyrophosphates, mixed phosphates, sulfates, and silicates. We also discuss the remaining challenges and corresponding strategies for polyanion-type materials. We hope this review can provide some insights into the development of polyanionic materials. This review summarizes the recent progress and remaining challenges of polyanion-type cathodes, providing guidelines towards high-performance cathodes for sodium ion batteries.